Generalised Random Categorisation Rules - Matthew Ryan (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2019)
Aguiar's (2017) random categorisation rule (RCR) describes random choice behaviour as the maximisation of a linear preference order over the intersection of a random consideration set with the set of available options. A key axiom in Aguiar's (2017) characterisation of the RCR is an acyclicity condition on a revealed preference relation derived from the random choice function. We show that this condition may be substantially weakened - to asymmetry of the revealed preference relation - without jeopardising the essence of the RCR representation. In our generalisation of the RCR, preferences may be ill-behaved on subsets of alternatives that are never considered together. While these pathologies in preference are masked by the decision-maker's selective attention to an particular choice problem, they may still be revealed by data across dierent choice problems. Finally, we show that the generalised model remains within the random utility class.
Keywords: 330